1987
DOI: 10.1108/eb001431
|View full text |Cite
|
Sign up to set email alerts
|

Museums and Marketing Techniques

Abstract: The present day museum is a far cry from the original concept but is it what the public wants?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Although some evidences demonstrated that the museum research had been poorly designed and conducted (Yorke and Jones, 1987), this study was designed to discover the needs and wants, interests and satisfaction level of all visitors so that the 24 museum sites around the state of Pennsylvania can serve them better. In addition, it aimed to determine service quality in Pennsylvania's Museums and Historical sites, and to be able to reach the target visitors and communicate with them through various broadcast, electronic and print media such as radio, television, magazines, newspapers, brochures, pamphlets, and Internet.…”
Section: Purpose Of the Studymentioning
confidence: 99%
See 3 more Smart Citations
“…Although some evidences demonstrated that the museum research had been poorly designed and conducted (Yorke and Jones, 1987), this study was designed to discover the needs and wants, interests and satisfaction level of all visitors so that the 24 museum sites around the state of Pennsylvania can serve them better. In addition, it aimed to determine service quality in Pennsylvania's Museums and Historical sites, and to be able to reach the target visitors and communicate with them through various broadcast, electronic and print media such as radio, television, magazines, newspapers, brochures, pamphlets, and Internet.…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…They offer an informal environment for learning and fulfilling educational needs of visitors (Yorke and Jones, 1987). However, museums should spend time, money and effort for identifying the needs and wants of their visitors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…I have been researching arts marketing since 1993 when I was completing my Masters thesis at the University of Ulster. At that time, the majority of work was North American in origin, with activities elsewhere in their infancy (Diggle, 1976;Raymond and Greyser, 1978;Diggle, 1984;Skinner, 1985;Yorke and Jones, 1987;Bradford, 1991;Cooper and Tower, 1993). Marketing had already been applied widely across profit and non-profit sectors in the USA for many decades (Kotler and Levy, 1969;Hunt, 1976;Shapiro, 1973;Kotler and Andreasen, 1991;Kotler and Scheff, 1997).…”
Section: Introduction: Early Arts Marketing Researchmentioning
confidence: 99%